O romance contemporâneo em Goiás - um estudo da narrativa ficcional "As lesmas" de Heleno Godoy - Procópio, Raphaela Pacelli (2022)
This doctoral thesis aims to expand the study already initiated in my master's degree, defended in 2011, about the writing of Heleno Godoy, contributing to the theoretical-critical collection of this writer, born in the state of Goiás. For that, we decided, in this new stage of this research, to emphasize the appreciation of the author's fictional narrative, selecting his only novel, “As Lesmas”, published for the first time in 1969 and reprinted in 2002. This book projected the literature made in the state of Goiás in the scenario of contemporary narratives and received the appreciation of several critics, such as Bernardo Élis (1970), Milton Cabral Viana (1970), Mário Chamie (1974), Afrânio Coutinho (1997), Carlos Fernando Magalhães (2002), Albertina Vicentini (2002) and Nelly Novaes Coelho (2013). Thus, this study intends to contribute to the improvement of Godoy's critical fortune and to the dissemination of a closer look at his work. To this intent, in addition of outlining an overview of literary manifestations in the state of Goiás in order to understand the process of artistic maturation until the creation of the GEN group, understood as a milestone for the literature from Goiás and of paramount importance for the work of the Godoyan artist, it will allow us to understand the context of writing and construction of the analyzed novel, especially the political and social events that permeated the last decades of Brazil, such as the military dictatorship that lasted from 1964 to 1985. In this sense, we will try to analyze what this fragmentary and deconstructed production, which is based on nonlinearity and the concurrency of information and imbrication of voices, has to tell us about postmodernity, one of the aesthetic perspectives of contemporary narrative, trying to identify which postmodern narrative procedures are present in the work. In general, we will analyze how this post-1964 production is structured, trying to understand how form and content are intertwined, because we know that more than telling a story, it is necessary to show how it is told. Furthermore, we will present how this fragmented narrative dissolves the unique meaning of the text, composing a mosaic of meanings that requires a self-reflective role of the reader on the reality presented: of love (homosexual) and of historical events (Military Coup of 1964).